Qualitative Analysis of Local Government Elections 2001: A Case Study of District Peshawar - Anwar, Salman (Annals of Human and Social Sciences, 2024)
The aim and objective of this paper is to analyse local government elections 2001 in district Peshawar, Khyber Pakhtunkhwa, Pakistan. Local government is a very significant tier of governance in democratic societies. It manages the affairs of government at grass root level i.e. villages, towns, tehsils and districts. Pakistan inherited a more controlled and centralized local government system from British India after its inception in 1947. Unfortunately this important tier of governance did not developed with the passage of time in Pakistan. The devolution of power plan 2001 was an important step taken by General Pervez Musharraf. Reforms were introduced in civil bureaucracy and police and local bodies were strengthened. The study is based on qualitative method with Interviews, personal observations and common masses perceptions about the local government system in Pakistan. Results shows a power struggle between MNA’s, MPA’s and Nazims after the general elections in 2002. Bureaucracy with their colonial mindset succeeded in getting their powers back with the help of first tier of government.